2005
DOI: 10.1002/adfm.200400054
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Field‐Effect Mobility Due to Surface‐Mediated Molecular Ordering in Regioregular Polythiophene Thin Film Transistors

Abstract: With the aim of enhancing the field‐effect mobility by promoting surface‐mediated two‐dimensional molecular ordering in self‐aligned regioregular poly(3‐hexylthiophene) (P3HT) we have controlled the intermolecular interaction at the interface between P3HT and the insulator substrate by using self‐assembled monolayers (SAMs) functionalized with various groups (–NH2, –OH, and –CH3). We have found that, depending on the properties of the substrate surface, the P3HT nanocrystals adopt two different orientations—pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
284
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 454 publications
(297 citation statements)
references
References 34 publications
12
284
1
Order By: Relevance
“…13,17,66,[69][70][71][72] As mentioned above, the structural and optical analyses are bulk measurements, whereas transport measurements in the context of OTFTs is far more sensitive to the polymer order and conformation at the interface. 11 Since surface functionalization has an enhancing effect limited to within approximately 10 nm of the modified interface, 11,40 we speculate that the measured improvements in local order averaged over the entire film depth may be even more pronounced at the interface, perhaps explaining the dramatic enhancement of carrier mobility by nearly two orders of magnitude.…”
Section: Local Order In P3ht Filmsmentioning
confidence: 99%
See 3 more Smart Citations
“…13,17,66,[69][70][71][72] As mentioned above, the structural and optical analyses are bulk measurements, whereas transport measurements in the context of OTFTs is far more sensitive to the polymer order and conformation at the interface. 11 Since surface functionalization has an enhancing effect limited to within approximately 10 nm of the modified interface, 11,40 we speculate that the measured improvements in local order averaged over the entire film depth may be even more pronounced at the interface, perhaps explaining the dramatic enhancement of carrier mobility by nearly two orders of magnitude.…”
Section: Local Order In P3ht Filmsmentioning
confidence: 99%
“…11 Importantly it has been suggested that surface functionalization has an enhancing effect on interfacial order, with the effect limited to within approximately 10 nm of the modified interface, 11,40 which means that the increased molecular order of polymer film at the interface with the OTS-treated substrate may arise from the increased interfacial order in very thin (less than ca. 10 nm) P3HT layer.…”
Section: Otft Device Performancementioning
confidence: 99%
See 2 more Smart Citations
“…In the realm of semiconductive polymers, large single rectangular crystals of 3-hexyl thiophene (3HT) 8 [35,36], nanowires of conjugated poly(p-phenylene ethynylene) derivatives [37], poly(3-hexyl thiophene) (P3HT) nanowhiskers [38], one-dimensional (1D) microwire P3HT single crystals [39], and self-organized two-dimensional (2D) P3HT supramolecules [40,41] were reported. Nascent lateral habits of solution-grown single crystals [42], surface-patterned single crystals [43][44][45][46][47], and conductive-dielectric-conductive single crystals [48][49][50] have also been reported.…”
Section: Introductionmentioning
confidence: 99%